The survey of economic growth, energy consumption and carbon emission - Waheed, Rida; Sarwar, Sahar; Chen, Wei (Energy reports, 2019)
The study aims to examine the survey of earlier literature that deals with economic growth, energy consumption and carbon emission, both single country studies as well as multi-county studies that covers the period till 2019. The main focus of this survey is on the coverage of countries, modeling methodologies, periods as well as empirical conclusions. The literature survey in this research paper is based on the causality's direction between (i) economic growth and carbon emission; (ii) economic growth and energy consumption; (iii) energy consumption and carbon emissions. From reviewing these studies, general remark can be assumed that the literature which has been produced is paradoxical. Firstly, most of the earlier studies have reported that economic growth and energy consumption are significant sources of carbon emission, however, the role of economic growth in carbon emission is highly reported in highly developing countries. On contrary, in case of developed countries, carbon emission is not linked with economic development. Secondly, in case of developing countries, higher energy consumption leads to increase the economic growth. For developed countries, there are less evidence of dependence between energy consumption and economic growth. Lastly, in both developing and developed countries, higher energy consumption has reported the main culprit for carbon emission Focusing on the implications, the governments and industries have to replace the non-renewable energy sources with renewable sources to generate electricity, run the industrial operations and for transportation purposes etc. Comprehending the literature survey has provided the basis to address the designing as well as implementing effective environmental as well as energy policies.